Evaluation of Nursing Knowledge and Practices Concerning Nursing Care of Patient with Skin Traction in Orthopedic Units in Kurdistan Region - Al-Attar, wafaa; Al-Barwari, ronak; Sae’ed, omer (Iraqi National Journal of Nursing Specialties, 2006)
Objective: The study aimed to evaluate knowledge and practices of nursing staff at the orthopedic unitsregarding the existing care of patient with skin traction.Methodology: The sample consists of (40) nurses, (20) of them from Emergency Teaching Hospital in Duhokand the other (20) of them from Erbil Teaching Hospital in Erbil from 1st Dec. 2004 to the end of June 2005 inKurdistan Region.Two instruments were constructed to evaluate knowledge and practices. Evaluation of knowledge was done byusing of multiple choice questions composed of (25) questions, and evaluation of practice was done by using theobservational check list which consist of four main category (pre skin traction, during skin traction, post skintraction and follow up of patient have skin traction).Validity of questionnaire was determined through the expert.Results: Indicated that the nurses knowledge scores was satisfied about patient have skin traction in Duhok andErbil.In relation to the evaluation of nurses’ practice, it was found that the practices of the nurses were inadequate inDuhok and Erbil Hospitals.The study founded there was no significant difference between Duhok and Erbil of knowledge and practices.The finding indicated that there was no significant relationship between nurses’ knowledge and practices andyears of experience in orthopedic units.Recommendation: The number of staff should be increased in orthopedic units, education and special trainingprograms for these nurses in orthopedic units should be designed and presented through how to provide nursingcare, how to prevent complications and management of complications if present.